Morphological and functional characterization of cow oocytes for assisted reproduction techniques - Opizzo Balza, Bianca Ana (2023)
In in vitro production of embryos (IVP), oocytes from the ovaries of slaughterhouse animals are commonly used. However, the quality of these oocytes is highly variable due to unknown category and condition of the slaughtered females. As a result, a heterogeneous population of oocytes with varying capacities for maturation and supporting embryonic development is obtained. The aim of this study was to investigate the morphological and biological characteristics of ovaries and oocytes from slaughtered bovines in order to establish selection criteria for oocytes to be used in IVP. To achieve this, the ovaries were categorized based on the presence or absence of structures such as Corpus Luteum (CL), Dominant Follicle (DF), both (CL+DF), or none (NO). The number and diameter of the follicles were also determined and grouped into three categories: <3 mm, 3-8 mm, or >8 mm. The Cumulus-Oocyte Complexes (COCs) obtained through follicular aspiration were analyzed for several parameters. These included, oocyte coverage by the Cumulus Cells (CC), the number of layers of CC, compaction and thickness of the CC layers. In denuded oocytes, the area, perimeter and diameter of the ooplasm as well as the thickness of the Zona Pellucida (ZP) were measured. Additionally, staining with Hoechst 33342, propidium iodide, or Rhodamine 123 was performed to analyze nuclear and metaphase morphology, cell viability, and mitochondrial functionality, respectively. All these determinations were made on photomicrographs captured using a camera attached to an inverted microscope and processed using the Fiji software. Statistical analysis was conducted using ANOVA and Bonferroni Test. The results revealed a predominance of ovaries with CL+DF, and in terms of follicular size, the <3 mm category exhibited the highest frequency of follicles, followed by the 3-8 mm category. Approximately 87.83±6.51% of the COCs showed complete coverage by CC; with 69.66±7.86% of the CC exhibiting compaction and 21.92±7.86% being slightly relaxed. A correlation was observed between the variable of CC layers and CC diameter (quantitative), with 91.42% of COCs having maximum diameters. Approximately, 83.11±4.27% of the oocytes displayed homogenous ooplasm, with the following measurements: area 12±0.37µm2 , perimeter 387.5±10µm, diameter 123±1.1µm, and ZP thickness 12.2±0.17µm. Moreover, 97.61± 0.11% of the oocytes were found to be viable, with no alterations observed in nuclear morphology and 100% displayed mitochondrial and metaphase activity. In conclusion, the ovaries and their corresponding COCs obtained from slaughtered females exhibit characteristics indicative of good quality for use in in vitro procedures.